Evaluation of a new tablet formulation of deferasirox to reduce chronic iron overload after long-term blood transfusions - Chalmers AW; Shammo JM (Dove Medical Press, 2016)
Anna W Chalmers, Jamile M Shammo Department of Internal Medicine, Division of Hematology/Oncology, Rush University Medical Center, Chicago, IL, USA Abstract: Transfusion-dependent anemia is a common feature in a wide array of hematological disorders, including thalassemia, sickle cell disease, aplastic anemia, myelofibrosis, and myelodysplastic syndromes. In the absence of a physiological mechanism to excrete excess iron, chronic transfusions ultimately cause iron overload. Without correction, iron overload can lead to end-organ damage, resulting in cardiac, hepatic, and endocrine dysfunction/failure. Iron chelating agents are utilized to reduce iron overload, as they form a complex with iron, leading to its clearance. Iron chelation has been proven to decrease organ dysfunction and improve survival in certain transfusion-dependent anemias, such as β-thalassemia. Several chelating agents have been approved by the United States Food and Drug Administration for the treatment of iron overload, including deferoxamine, deferiprone, and deferasirox. A variety of factors have to be considered when choosing an iron chelator, including dosing schedule, route of administration, tolerability, and side effect profile. Deferasirox is an orally administered iron chelator with proven efficacy and safety in multiple hematological disorders. There are two formulations of deferasirox, a tablet for suspension, and a new tablet form. This paper is intended to provide an overview of iron overload, with a focus on deferasirox, and its recently approved formulation Jadenu® for the reduction of transfusional iron overload in hematological disorders. Keywords: iron chelation therapy, transfusional iron overload, deferasirox